GRB2 promotes brain metastasis in HER2-positive breast cancer by regulating the Ras/MAPK pathway - Hongyu Li; Yalin Zhang; Xiao Han; Bingyu Li; Dan Liu; Gang Sun (Scientific Reports)
Abstract Brain metastasis is emerging as the most serious concern for breast cancer patients. HER2-positive breast cancer is more prone to undergo brain metastasis than other subtypes; notably, there has been little improvement in the treatment of brain metastasis .Our study confirmed the relevance of HER2 status to brain metastasis risk via clinical data analysis and revealed that exerts GRB2 tumorigenic effects by regulating the Ras/MAPK pathway in vivo and in vitro. Both an in situ injection model and a direct cerebral injection model were used to explore the ability of GRB2 to promote the brain metastasis. Results indicated that HER2- positive is a risk factor for brain metastasis according to clinical data. GRB2 enhances proliferation, migration, and invasion while suppressing apoptosis in HER2-positive breast cancer cells in vitro, primarily by regulating phosphorylation and alternative splicing of key proteins within the Ras/MAPK pathway. Notably, tumor cells were able to cross the blood‒brain barrier in both models assessed in this study. Thus, GRB2 is an oncogenic factor that contributes to the malignancy of HER2-positive breast cancer, GRB2 and HER2 can synergistically promote tumor cell penetration of the blood‒brain barrier and induce metastasis.